Magnetic Actuators: Reconfigurable Magnetic Origami Actuators with On‐Board Sensing for Guided Assembly (Adv. Mater. 25/2021). Issue 25 (22nd June 2021) - Ha, Minjeong; Cañón Bermúdez, Gilbert Santiago; Liu, Jessica A.‐C.; Oliveros Mata, Eduardo Sergio; Evans, Benjamin A.; Tracy, Joseph B.; Makarov, Denys
Abstract : In article number 2008751, Joseph B. Tracy, Denys Makarov, and co‐workers fabricate ultrathin and reconfigurable magnetic origami actuators equipped with highly compliant magnetic field sensors allowing detection of their magnetization state and control over complex assembly tasks. This functionality is of major importance to assure a proper fault‐free operation of origami‐based reconfigurable smart actuators, which are in the heart of strain‐engineered 3D architectures and soft robotics.